Dewas' Legal Effects on KPK Independence: A View from Siyasah Dusturiyyah - Haryani, Yeni; Irwansyah, Irwansyah (Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
This article says that the Supervisory Board's (Dewas) main job is to keep an eye on how the Corruption Eradication Commission (KPK) is doing. This includes making performance goals, managing the budget, and keeping an eye on wiretapping and searches done by the KPK. The goal of this paper is to explain, from the point of view of Siyasah Dusturiyyah, how the presence of the Supervisory Board in Law No. 30 of 2002 about the KPK affects the independence of the KPK. In this study, normative legal research was used. For this study, library research was used to find legal information. Based on the results of this study, Siyasah Dusturiyyah thinks that the presence of the Supervisory Board has a positive effect on the independence of the KPK. The Supervisory Board is an independent body that makes sure the KPK follows the law and isn't affected by political or other groups' interests. Artikel ini berusaha menegaskan tugas utama Dewan Pengawas (Dewas) adalah mengawasi bagaimana kinerja Komisi Pemberantasan Korupsi (KPK). Hal ini termasuk menetapkan sasaran kinerja, mengelola anggaran, dan mengawasi penyadapan dan penggeledahan yang dilakukan oleh KPK. Tulisan ini bertujuan untuk menjelaskan, dari sudut pandang Siyasah Dusturiyyah, bagaimana keberadaan Dewan Pengawas dalam UU No. 30 Tahun 2002 tentang KPK mempengaruhi independensi KPK. Dalam penelitian ini digunakan penelitian hukum normatif. Berdasarkan hasil kajian tersebut, Siyasah Dusturiyyah menilai kehadiran Dewan Pengawas berpengaruh positif terhadap independensi KPK. Dewan Pengawas adalah badan independen yang memastikan KPK taat hukum dan tidak terpengaruh oleh kepentingan politik atau kelompok lain.